The companion as a protagonist in the prevention of infections in patients in the hospital environment: an experience report (Research, Society and Development, 2022)
Objective: To report the experience of nursing students on the role of the companion in the prevention of infection to patients hospitalized in the hospital environment. Methodology: This is a descriptive study, of the experience report type, with a qualitative approach, bringing the experiences of nursing students from the University Center of the Metropolitan Region of Belém do Pará during educational activities in six wards of a surgical center in a reference hospital in women's health care in the state. Results: Through an educational action, the main care to be carried out by the companions/visitors was emphasized, through a folder, a step by step of the correct way of hand hygiene and other useful tips to prevent hospital infections, the importance of these care to combat “superbacteria” and a short word search in the process of gamification and knowledge fixation and, finally, there was the moment to remove doubts. Final Considerations: The educational actions carried out in the wards allowed the companions and patients to have a breadth of knowledge about the importance of their preventive measures for the patient's health, implementation of infection control and continuing education as strategies to implement effective measures in the pursuit of quality of care.